Effect of high pressure on conductivity in the basal plane of Y₁₋xPrxBa₂Cu₃O₇₋δ single crystals lightly doped of praseodymium - Khadzhai, G.Ya.; Vovk, N.R.; Vovk, R.V.; Savich, S.V.; Kislitsa, M.; Kotvitskaya, K.A.; Morozov, V.S.; Leniv, J.G.; Timofeev, S.S. (Functional Materials, 2014)
Effect of high hydrostatic pressure up to 17 kbar on conductivity of lightly Pr-doped Y₁₋xPrxBa₂Cu₃O₇₋δ (x~0.05) single crystals is investigated. We show that in contrast to non-doped YBa2Cu3O7-δ samples, application of the high pressure leads to a substantial increase of the pressure derivative of the coherence length dξc/dP and temperature shift of 2D-3D crossover point. Possible mechanisms of the influence of the high pressure on the critical temperature and the coherence length are discussed within the frames of a model assuming the presence of singularities in the charge carriers electron spectrum typical for lattices with strong coupling. The excess conductivity Δ σ(T) inY₀.₉₅xPr₀Ba₂Cu₃O₇₋δ has beenY0.95Pr0.05Ba2Cu3O7-δ revealed to obey an exponential dependence in the wide temperature range Tf < T < T*. At this, description of the excess conductivity by the expression Δ σ ~ (1 - T/T*)exp(Δ*ab/T) can be interpreted in terms of the mean-field theory, where T* is the mean-field superconducting transition temperature and pseudogap temperature dependence is satisfactory described within the framework of the BCS-BEC crossover theory. An increase of the applied pressure leads to narrowing of the temperature range of realization of the pseudogap regime, thereby expanding the linear temperature dependence of the basal-plane resistivity ρab(T).